Creativity in local government: definition and determinants - Kruyen, Peter M.; Genugten, Marieke van (2017)
In current thinking about public service improvement, civil servant creativity plays an important role. Using the results of 43 semi-structured interviews, we assessed the degree to which our theoretical knowledge about creativity-based primarily on business research-matches the insights of managers in local government. Respondents considered employee creativity to be important, but-in contrast to the literature-understood creativity as the act of trying out new things to better deal with specific problems at hand instead of developing new ideas potentially applicable to a wider context. As such, respondents did not see creativity as the main precondition for innovation. In line with the literature, there is little consistency across respondents about individual- and context-level determinants of creativity. Lastly, respondents put forward several factors that have received little attention in the literature but are particularly relevant in understanding differences in work-related creativity in the context of local government. - Reproduced.
Keywords: Local government